Clinical progression and changes of chest CT findings among asymptomatic and pre-symptomatic patients with SARS-CoV-2 infection in Wuhan, China. (4th March 2021) - Yang, Rongrong; Gui, Xien; Gao, Shicheng; Ke, Hengning; Xiong, Yong
ABSTRACT: Objectives: To analyze characteristics of asymptomatic/pres-ymptomatic patients with SARS-CoV-2 infection. Methods: Chest computed tomography(CT), indicators for organ and coagulation function, inflammation cytokines, of asymptomatic/pre-symptomatic patients with SARS-CoV-2 infection were retrospectively analyzed in Zhongnan Hospital of Wuhan University from 20 December 2019, to 8 March 2020. Results: The proportion of normal chest CT in asymptomatic and pre-symptomatic patients with SARS-CoV-2 infection were 35.4% (17/48) and 3.3%(2/61), respectively ( P < 0.001). In 17 asymptomatic patients, their images of chest CT maintained normal during the whole course of diseases, while the normal images of chest CT in 2 pre-symptomatic patients progressed to abnormal later ( P < 0.001). All the six asymptomatic patients with SARS-CoV-2 infection maintained unilateral lesion, while the proportion was 29.4%(5/17) in pre-symptomatic patients( P = 0.003). Compared with asymptomatic patients, pre-symptomatic COVID-19 patients had worse levels of Lymphocyte count ( P = 0.001), Albumin ( P = 0.045), Aspartate aminotransferase ( P = 0.044), γ-glutamyl transpeptadase ( P = 0.016), Globulin ( P = 0.036), Creatinine ( P = 0.021), Lactate dehydrogenase ( P = 0.008), C-reactive protein ( P < 0.001), Serum amyloid A ( P < 0.001), and Erythrocyte sedimentation rate ( P < 0.001). Except for above indicators, Alkaline phosphatase ( P = 0.009), Procalcitonin ( P = 0.010), and D-dimer( P < 0.001) increased further during periods of symptoms compared with those levels in pre-symptomatic period. Conclusion: In early stage after SARS-CoV-2 infection, images of chest CT and blood tests of asymptomatic patients were different from pre-symptomatic patients.